2021
DOI: 10.3892/mmr.2021.12311
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl itaconate inhibits LPS‑induced microglia inflammation and inflammasome‑mediated pyroptosis via inducing autophagy and regulating the Nrf‑2/HO‑1 signaling pathway

Abstract: The endogenous metabolite itaconate and its cell-permeable derivative dimethyl itaconate (DI) have been identified as anti-inflammatory regulators of macrophages; however, their contribution to inflammasome-mediated pyroptosis remains unknown. The present study examined the molecular mechanism of DI on NLR family pyrin domain-containing 3 (NLRP3) inflammasome assembly and NLRP3 inflammasome-dependent pyroptosis in microglia. Lipopolysaccharide (LPS) and ATP were used to induce microglia pyroptosis in vitro; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Consistently, our data showed that quercetin inhibits the tumorigenesis of CRC via inhibiting the polarisation of M2 macrophages. On the other hand, it has been reported that autophagy activation leads to the polarisation of macrophages ( Yang S. et al, 2021 ; Yang Y. et al, 2021 ). The present research indicates that autophagy induces the polarisation of M2 macrophages and that quercetin inhibits the autophagy in M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our data showed that quercetin inhibits the tumorigenesis of CRC via inhibiting the polarisation of M2 macrophages. On the other hand, it has been reported that autophagy activation leads to the polarisation of macrophages ( Yang S. et al, 2021 ; Yang Y. et al, 2021 ). The present research indicates that autophagy induces the polarisation of M2 macrophages and that quercetin inhibits the autophagy in M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, M2 macrophages are characterized by expressing high levels of IL-10 and Arg1 to relieve the inflammatory condition (Sica and Mantovani, 2012). A recent study found that DI promoted the transition from M1 to M2, reducing the expression of inflammatory mediators in microglia treated with LPS and ATP (Yang et al, 2021). In our study, DI promoted Arg1 and CD206 and inhibited the expression of iNOS and CD86 in CFA-treated paw tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Itaconate derivatives, when cultured with microglia stimulated with LPS + ATP, inhibit the NLRP3 inflammasome and IL-1β release. (Yang et al, 2021).…”
Section: Idh2mentioning
confidence: 99%